Rescaling White Space in Post‐apartheid Johannesburg. Issue 5 (25th March 2013) - Clarno, Andy
Abstract This paper traces three political mobilizations in the wealthy suburbs of Johannesburg: a boycott of redistributive tax policies, the creation of gated communities and residents' associations, and the demand for residential city improvement districts (CIDs). I argue that state rescaling and networked governance are constituted through struggles over governmental power. I also argue for more attention to race in the political economy of scale. Struggles over the scalar, networked, and territorial dimensions of governance are constitutive moments in the shifting articulation of race, class, and space. An analysis of articulation highlights the role of territory, identity and imagination in the production of space, demonstrates that neoliberal forms of networked governance are products of struggle, and reiterates the feminist argument that governmental interventions are about more than just capital accumulation.